AKUNTANSI ASET TETAP : PENTINGKAH STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK BAGI KOPERASI - Gaudensia Imelda; Sultan Syah; Ayu Gustiningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2021)
This study aims to determine the suitability of the accounting treatment of fixed assets in Lotus Cooperative Satbrimob Polda SulSel with Standards Accounting Financial Entity Without Accountability Public Number 15. The type of data is quantitative data and the data sources used are primary data and secondary data. The analytical method used is a comparative analysis method with an instrumental case study approach is a case study research conducted to examine a case and provide understanding or re-explain a brief process of events (generalization). Data collection techniques used are observations, interviews, and documentation. The results of the study said that the accounting treatment of fixed assets in Lotus Cooperative Satbrimob Polda Sulsel is in accordance with the Standards Accounting Financial Entity Without Accountability Public Number 15.